Effect of Brittle Mineral Size on Hydraulic Fracture Propagation in Shale Gas Reservoir. (30th January 2019) - Gao, Wei; Iqbal, Javed; Xu, Dan; Sui, Haoyue; Hu, Ruilin
Abstract : The properties of brittle minerals have great effect on the morphology of postfracturing network in shale reservoirs in the southeastern Ordos Basin, China. In order to study the effect of brittle mineral size distributions on the fracture parameters, the concrete cubes of 300 mm × 300 mm × 300 mm in size with four distinct brittle mineral sizes of 2.36 mm, 0.425 mm, 0.15 mm, and 0.075 mm were investigated under large-sized triaxial hydraulic fracturing test. The effect mechanism of aggregate on the fracture properties of shale was studied using ultrasonic technique, photosensitive electron microscope, and numerical simulation. The test results obtained for each specimen (both disturbed and undisturbed conditions) indicate that brittle mineral size has significant effect on the fracture extension. The tensile strength, fracture toughness, and fracture pressure were found to decrease with a decrease in maximum brittle mineral size when the maximum brittle mineral size is smaller than 0.425 mm. In addition to this, the degree of attenuation difference also follows the similar trend. Observed fracture morphology reveals that with an increase in maximum size of brittle mineral specimen, the tortuous and complicated cracking path generation increases. These findings would be very helpful in order to better understand the behavior of shale under hydraulic fracturing test.